2010
DOI: 10.5251/abjna.2010.1.5.961.968
|View full text |Cite
|
Sign up to set email alerts
|

Culture fisheries in village ponds: a multi-location study in Haryana, India

Abstract: The state of Haryana in northeastern India has an excellent sub-tropical climate for the development of fresh water fish culture in a variety of aquatic bodies. Aquaculture not only plays an important role in nutrition but also in the rural economy of the State. The main purpose of the present study was to identify the primary production and fish production patterns in village ponds under different management practices. With a more or less narrow range of primary production, varying fish production and growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 16 publications
7
60
0
Order By: Relevance
“…According to Bhatnagar and Singh (2010) and Bhatnagar et al (2004) DO level > 5 ppm is essential to support good fish production. Bhatnagar et al (2004) also suggests that DO levels of 1-3 ppm has sub lethal effect on growth and feed utilization, while DO levels of 0.3-0.8 ppm is lethal to fishes.…”
Section: Specific Growth Rate (%/Day) and Physico-chemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Bhatnagar and Singh (2010) and Bhatnagar et al (2004) DO level > 5 ppm is essential to support good fish production. Bhatnagar et al (2004) also suggests that DO levels of 1-3 ppm has sub lethal effect on growth and feed utilization, while DO levels of 0.3-0.8 ppm is lethal to fishes.…”
Section: Specific Growth Rate (%/Day) and Physico-chemical Parametersmentioning
confidence: 99%
“…Maximum limit of ammonia concentration for aquatic organisms is 0.1 mg/L (Santhosh and Singh, 2007), while Bhatnagar and Singh (2010) recommended that ammonia levels of < 0.2 mg/l are suitable for pond fishery. Consistent with these scholars, it was noted in the current study that the highest SGR for the control pond was registered at an ammonia level of 0.01 mg/l, which was within the recommended < 0.2 mg/l ammonia for fish culture in ponds.…”
Section: Specific Growth Rate (%/Day) and Physico-chemical Parametersmentioning
confidence: 99%
“…DO level greater than 5.0 mg/L is essential to support good fish production (Bhatnagar et al, 2004). Catfish and other air breathing fish can, however, survive in oxygen concentration as low as 1.0 mg/L (Santhosh and Singh, 2007;Bhatnagar and Singh, 2010;RFP, 2010;Infonet Biodivision, 2016;Swan, 2017). According to Banerjea (1967), DO between 3.0 and 5.0 mg/L in ponds is unproductive.…”
Section: Dissolved Oxygen (Do)mentioning
confidence: 99%
“…Clerk (1986) reported that BOD range of 2 to 4 mg/L does not show pollution level of concern while levels beyond 5 mg/L are indicative of serious pollution. The recommended optimum BOD for aquaculture ponds is a maximum of 10 mg/L (Santhosh and Singh, 2007;Bhatnagar and Singh, 2010;Mayer, 2012). The greater the BOD, the more rapidly oxygen is depleted.…”
Section: Bod 5 and Codmentioning
confidence: 99%
“…According to OATA (2008) the levels below 0.02 ppm were considered safe. Bhatnagar and Singh (2010) recommended the level of ammonia (<0.2 ppm) suitable for pond fishery. So, the result was safe for MSP but slightly harmful for HSP.…”
Section: Water Quality Parametersmentioning
confidence: 99%